Selected Decisions Supplement (10th Ed). (Selected Decisions; Issue, Year, 1984)
This paper presents Selected Decisions and Selected Documents' Supplement to Tenth issue of the IMF. This Supplement to the Tenth Issue of Selected Decisions of the IMF and Selected Documents contains decisions of a general nature adopted by the IMF since April 30, 1983, the date of publication of the Tenth Issue. Decisions of the IMF that are incorporated in the Rules and Regulations are not reproduced in this volume. The Executive Board approves the proposed method of applying the three-month rule for implementing the procedures for surveillance, set forth in EBD/83/161. The Executive Board has reviewed the document 'Surveillance over Exchange Rate Policies' as provided in paragraph 2 of the Executive Board Decision No. 5392-(77/63), adopted April 29, 1977, and will review it again at an appropriate time not later than April 1, 1986.